ACOUSTIC INVARIANT APPROACH TO SPEECH SOUND ANALYSIS FOR BRAND NEW SPEECH RECOGNITION SYSTEMS (UKRAINIAN AND ENGLISH) - Vakulenko, Maksym O. (International Journal of Computing, 2014)
On the basis of acoustic invariant speech analysis (AISA), the permanent spectral characteristics of the Ukrainian vowels are obtained for various ways of pronunciation including ordinary speech, whisper and changing tone. It is shown that the lowest phonemic frequencies due to vocal fold oscillations or to Helmholtz resonance are not associated with persistent sound features. It is conjectured that the only phonemic invariant is the ratio between formant frequencies, not their absolute values. This analysis is complemented by the computer sound synthesis. We show also that the acoustic invariants of the Ukrainian sound [i] are close to that of English [I]. The results obtained may be useful for specialists in the field of experimental phonetics and speech modelling.